Effects of Ecklonia stolonifera extract on the obesity and skeletal muscle regeneration in high-fat diet-fed mice. (July 2021) - Jin, Heegu; Oh, Hyun-Ji; Kim, Junghee; Lee, Kang-Pyo; Han, Xionggao; Lee, Ok-Hwan; Lee, Boo-Yong
Graphical abstract: Highlights: ESE reduces body mass gain in HFD-fed mice. ESE inhibits lipid accumulation and increase energy expenditure in WAT. ESE stimulates mitochondrial biogenesis and myogenesis in the skeletal muscle. Abstract: Obesity and metabolic diseases, such as diabetes, are associated with higher levels of lipid deposition in white adipose tissue (WAT). Recent studies have shown that obesity can lead to skeletal muscle loss, which results in the loss of skeletal muscle mass and strength. We aimed to determine whether Ecklonia stolonifera extract (ESE) protects mice against the obesity, obesity-related metabolic defects, such as hyperglycemia, and skeletal muscle loss that are induced by high-fat diet (HFD)-feeding. C57BL/6 mice were fed a chow diet (CD), an HFD to induce obesity, or an HFD supplemented with ESE for 6 weeks. At the end of the experimental period, the HFD group became obese, whereas the CD group did not. However, the ESE-treated group had lower body mass and blood glucose concentration. The skeletal muscle mass and grip strength of the ESE group tended to be higher than those of the HFD group. Moreover, skeletal muscle mitochondrial energy expenditure was increased by ESE, and this was accompanied by higher expression of myogenic regulatory factors (MRFs). These findings suggest that ESE can prevent the skeletal muscle loss that is associated with HFD-induced obesity and hyperglycemia.